2021 European Myeloma Network review and consensus statement on smoldering multiple myeloma: how to distinguish (and manage) Dr. Jekyll and Mr. Hyde - Musto, Pellegrino; Engelhardt, Monika; Caers, Jo; Bolli, Niccolo'; Kaiser, Martin; Van de Donk, Niels; Terpos, Evangelos; Broijl, Annemiek; De Larrea, Carlos Fernández; Gay, Francesca; Goldschmidt, Hartmut; Hajek, Roman; et al. (Haematologica, 2021)
According to the updated International Myeloma Working Group criteria, smoldering multiple myeloma (SMM) is an asymptomatic plasma cell disorder characterized by an M-component >3 g/dL, bone marrow plasma cell infiltration >10% and <60%, and absence of any myeloma-defining event. Active multiple myeloma is preceded by SMM, with a median time to progression of approximately 5 years. Cases of SMM range from the extremes of "monoclonal gammopathy of undetermined significance-like", in which patients never progress during their lifetimes, to "early multiple myeloma", in which transformation into symptomatic disease, based on genomic evolution, may be rapid and devastating. Such a "split personality" makes the prognosis and management of individual patients challenging, particularly with regard to the identification and possible early treatment of high-risk SMM. Outside of clinical trials, the conventional approach to SMM generally remains close observation until progression to active multiple myeloma. However, two prospective, randomized trials have recently demonstrated a significant clinical benefit in terms of time to progression, and of overall survival in one of the two studies, for some patients with higher-risk SMM treated with lenalidomide ± dexamethasone, raising the question of whether such an approach should be considered a new standard of care. In this paper, experts from the European Myeloma Network describe current biological and clinical knowledge on SMM, focusing on novel insights into its molecular pathogenesis, new prognostic scoring systems proposed to identify SMM patients at higher risk of early transformation, and updated results of completed or ongoing clinical trials. Finally, some practical recommendations for the real-life management of these patients, based on Delphi consensus methodology, are provided.
Keywords: doutnající mnohočetný myelom; Multiple Myeloma; mnohočetný myelom; rizikové faktory; progrese nemoci; Humans; prospektivní studie; lidé; Monoclonal Gammopathy of Undetermined Significance; monoklonální gamapatie nejasného významu; Disease Progression; Smoldering Multiple Myeloma; Risk Factors; Prospective Studies